2012
DOI: 10.4049/jimmunol.1103271
|View full text |Cite
|
Sign up to set email alerts
|

A Coreceptor-Independent Transgenic Human TCR Mediates Anti-Tumor and Anti-Self Immunity in Mice

Abstract: Recent advancements in T cell immunotherapy suggest that T cells engineered with high affinity T cell receptors (TCR) can offer better tumor regression. However, whether a high affinity TCR alone is sufficient to control tumor growth, or the T cell subset bearing the TCR is also important remains unclear. Using the human tyrosinase epitope reactive, CD8 independent, high affinity TCR isolated from MHC class-I restricted CD4+ T cells obtained from tumor infiltrating lymphocytes of a metastatic melanoma patient,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 41 publications
4
52
0
Order By: Relevance
“…s3A). To confirm our results in a second model, we used the h3T TCR transgenic mouse, whose T cells recognize tyrosinase in an HLA-A2-restricted manner (37). h3T T cells activated in the presence or absence of IL-12 showed similar persistence when transferred into irradiated WT B6 or HLA-A2 transgenic mice (Fig.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…s3A). To confirm our results in a second model, we used the h3T TCR transgenic mouse, whose T cells recognize tyrosinase in an HLA-A2-restricted manner (37). h3T T cells activated in the presence or absence of IL-12 showed similar persistence when transferred into irradiated WT B6 or HLA-A2 transgenic mice (Fig.…”
Section: Resultsmentioning
confidence: 61%
“…IL-15 −/− mice were purchased from Taconic (Hudson, NY). H3T TCR transgenic mice were generated as previously described (32). Pmel-1 mice were maintained by crossing a pmel-1 (male) to a Thy1.1 (female) generating hemizygous offspring.…”
Section: Methodsmentioning
confidence: 99%
“…A comparative determination of the anti-tumor property between Th1, Th17 or Th1/17 cells differentiated ex vivo using melanoma epitope tyrosinase reactive CD4 + T cells obtained from h3T TCR transgenic mice (Mehrotra et al, 2012), showed that adoptive transfer of hybrid Th1/17 cells exhibit superior tumor control as compared to Th1, Th17 (Figure 2A) or even Th17 IL1β+TGFβ cells (Figure S2A). Administering anti-IFNγ or anti-IL17 antibody to the recipient mice along with ACT showed that IL17 neutralization had minimal effect on B16 tumor progression, at least during the initial three weeks, whereas blocking of IFNγ completely diminished the anti-tumor potential of Th1/17 cells (Figure 2B).…”
Section: Resultsmentioning
confidence: 99%
“…CD38KO-IFNγ Thy1.1 knock-in mice, HLA-A2 + -Rag −/− mice and Pmel-IFNγ −/− mice were developed in the lab. Melanoma epitope tyrosinase reactive HLA-A2 restricted TCR transgenic mouse (referred as h3T in the text) was developed in the lab and reported earlier (Mehrotra et al, 2012). Animals were maintained in pathogen-free facilities and experimental procedures were approved by Institutional Animal Care and Use Committees of Medical University of South Carolina, Charleston.…”
Section: Methodsmentioning
confidence: 99%
“…Development of h3T transgenic mouse bearing TCR reactive to the human tyrosinase 368–376 (YMDTMSQV) epitope has been described recently (14). OT-II-GFP-FoxP3 mice co-expressing EGFP and FoxP3 were kind gift from Dr. C. Vasu, MUSC.…”
Section: Methodsmentioning
confidence: 99%